Neonatal Immune Activation May Provoke Long-term Depressive Attributes - Schelder-Marzzani, Simone H.; Dias, Paula; Freiberger, Viviane; Ventura, Letícia; Silva, Bruna B.; Dutra, Matheus L.; Bobinski, Franciane; Schlindwein, Aline D.; Cassol, Omar J.; Comim, Clarissa M. (Current Neurovascular Research, 2019)
Background: Studies have shown the relationship between neuroinflammation and depressive- like parameters. However, research still has not been carried out to evaluate neuroinflammation in the neonatal period and psychiatric disorders in adulthood. Objective: To verify the association between neonatal immune activation and depressive-like parameters in adulthood using an animal model. Methods: Two days old C57BL/6 animals were exposed to lipopolysaccharides (LPS) or phosphate- buffered saline (PBS). When the animals were 46 days old, they received PBS or Imipramine at 14 days. At 60 days, the consumption of sucrose; immobility time; adrenal gland and the hippocampus weight; levels of plasma corticosterone and hippocampal Brain-derived neurotrophic factor (BDNF) were evaluated. Results: It was observed that the animals exposed to LPS in the neonatal period and evaluated in adulthood decreased the consumption of sucrose and had reducted hippocampus weight. Also, the exposed animals presented an increase of immobility time, adrenal gland weight and plasma levels of corticosteroids. The use of imipramine did not only modify the decreased hippocampal weight. On the other hand, there were no alterations in the BDNF levels in the hippocampus with or without the use of imipramine. Conclusion: These results suggest that neonatal immune activation may be associated with depressive- like parameters in adulthood. It is believed that endotoxemia may trigger physiological and behavioral alterations, increasing vulnerability for the development of depression in adulthood.
Keywords: Major Depressive Disorder (MDD)